Population pharmacokinetic analysis for dabigatran etexilate in Chinese patients with non-valvular atrial fibrillation - Liu, Ya-ou; Xie, Qiu-fen; Liu, Zhi-yan; Wang, Zhe; Mu, Guang-yan; Zhang, Ya-tong; Zhao, Zi-nan; Yuan, Dong-dong; Guo, Li-ping; Wang, Na; Xiang, Jing; Song, Hong-tao; et al. (Frontiers in Cardiovascular Medicine, 2022)
We aimed to develop a pharmacokinetic (PK) and pharmacodynamic (PD) model from healthy Chinese subjects and real-world nonvalvular atrial fibrillation (NVAF) patients. We also investigated meaningful intrinsic and extrinsic factors and related biomarkers for bleeding events. We characterized the integrated PK/PD models based on rich PK/PD data [dabigatran concentration, activated partial thromboplastin time (APTT), prothrombin time (PT), and anti-factor IIa (anti-FIIa) activity] from 118 healthy volunteers and sparse PD data [APTT, PT, and anti-FIIa] from 167 patients with NVAF after verifying the model extrapolation performance. We also documented the correlations between PD biomarkers and clinically relevant bleeding events over one year. Next, we used the final integrated PK/PD model (a two-compartment, linear model with first-order absorption) to evaluate the influence of dosage and individual covariates on PD parameters. The age, high-density liptein cholesterol (HDL-C), and creatinine clearance (CrCL) improved the PK model fit. The linear direct-effects PD model described the correlation between APTT, PT, and anti-FIIa and plasma concentration. CrCL improved the PD model fit. Anti-FIIa was more sensitive to the increase in dabigatran exposure than APTT and PT in the PD model. Therefore, fixed dabigatran doses could be prescribed for patients with NVAF without adjusting for age and HDL-C. We observed an elevated bleeding tendency with higher peak and trough values of APTT, PT, and anti-FIIa. Randomized studies should be performed to evaluate the efficacy and safety of low-dose dabigatran in Chinese patients with NVAF.